THE CHALLENGES OF ISLAMIC EDUCATION IN THE INDUSTRIAL ERA 4.0 - Karim, Mohammad; Fauziyah, Nailul (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
Today, the world has come into the Industrial Era 4.0. Everything is digital. Important information is very much provided, including the information related to Islamic Education (PAI). There have been changes and shifts on both sources and methods of learning PAI. This paper discusses the problems and challenges of PAI in the industrial era of 4.0. It is carried out in the interpretive paradigm with a qualitative approach through document study and content analysis. Industry 4.0 is the development of digital information technology which results in vertical and horizontal interconnectivity within one and among organizations, inter-region, and inter-continents with a no-time-limit in the flow of information and decision making. Technology becomes an unconscientious giant, a human creation which controls over human beings. There are major changes on the concept of values and teachings which will mainly become the focus of PAI.